Abdominal Wall Haematoma Complicating Laparoscopic Cholecystectomy. Issue 4 (1994) - Bhattacharya, S.; Tate, J. J. T.; Davidson, B. R.; Hobbs, K. E. F.
Abstract : Of 61 consecutive patients undergoing laparoscopic cholecystectomy, 4 (6.25%) developed abdominal wall haematomas. This complication of laparoscopic cholecystectomy may occur more commonly than existing literature suggests, and manifests in the post-operative period (days 2 to 6) by visible bruising, excessive pain or an asymptomatic drop in haematocrit. It is readily confirmed by ultrasonography. While no specific treatment is necessary apart from replacement of significant blood loss, the patient requires reassurance that this apparently alarming complication will rapidly resolve.